The First Translation of a Chinese Drama into a European Language: Le petit orphelin de la maison de Tchao. - Criscuolo, Catello (Monumenta Serica: Journal of Oriental Studies, 2021)
A partial translation of the Yuan dynasty drama The Orphan of the Zhao Family by the Jesuit missionary Joseph Henri-Marie de Prémare was published in Paris in 1735. As the first example of a Chinese theatrical work becoming known in Europe, the translation had a vast impact and gave rise to the composition of some European plays which, to varying degrees, were inspired by it. The present study focuses not on these adaptations, but on Prémare's translation itself. In recognising its central role both in the formation of a European perception of Chinese literature and in the history of the development of Sinology, this study is an investigation of the linguistic and cultural modalities through which Prémare managed to present to the European reader, at least in part, the moral tension that animates the drama, despite the objective difficulty present in every transcoding operation – especially in the earlier works – and the subjective ambition to provide an image of China that was not excessively "pagan."